THE INFLUENCE OF LIABILITY TO EQUITY RATIO ON FINANCIAL STABILITY OF PT BANK MANDIRI IN FINANCIAL REPORT AS OF JANUARY 31, 2025 - Valentina, Gladysia; Ayu, Tria; Fitriani, Ani Qotuzzuhro (Indragiri Research Center (ingreat), 2025)
This study analyzes the effect of the debt to equity ratio (DER) on the financial stability of PT Bank Mandiri (Persero) Tbk based on the financial report as of January 31, 2025. Bank Mandiri's DER was recorded as high at 6.35, meaning that every Rp1 of equity is supported by Rp6.35 in liabilities, indicating potential liquidity risks and dependence on external funds. However, despite the high DER, Bank Mandiri's financial stability is maintained thanks to good risk management, maintained asset quality, and solid financial performance, including the growth of third-party funds dominated by low-cost funds (CASA) and a low NPL ratio of around 1%. The study uses a descriptive quantitative method with secondary data from Bank Mandiri's balance sheet, including total liabilities and equity and their components. The theoretical study emphasizes the importance of a healthy capital structure with proportional management of liabilities and equity to maintain stability and customer trust and comply with banking regulations. In conclusion, the high DER does contain risks, but with disciplined risk management and good financial management, Bank Mandiri is able to maintain its financial stability. It is recommended that Bank Mandiri continue to strengthen capital, proactively manage risks, and innovate in financial services to maintain operational sustainability and stability amidst uncertain economic dynamics.